The DNH 7 skull of Australopithecus robustus from Drimolen (Main Quarry), South Africa. Issue 151 (February 2021) - Rak, Yoel; Kimbel, William H.; Moggi-Cecchi, Jacopo; Lockwood, Charles A.; Menter, Colin
Abstract: Although the early hominin species Australopithecus robustus has been known for more than eight decades and is represented by hundreds of fossils from sites in South Africa, a complete, well-preserved skull has been elusive. DNH 7, an adult cranium and mandible from the Drimolen site, was identified, on the basis of its small size, as a presumptive female of A. robustus . Here, we provide a detailed comparative description of the specimen. In cranial, facial, and dental size, DNH 7 is confirmed to lie at the extreme small end of the A. robustus range of variation, along with a few fragmentary maxillofacial specimens from Swartkrans. In addition, relative to the classically derived craniofacial features of the Swartkrans+Kromdraai portions of the A. robustus hypodigm, primitive anatomy pervades the DNH 7 face, braincase, and cranial base. Taken together, these pieces of evidence place DNH 7 in a previously unfilled position on the robust Australopithecus morphocline, where the specimen highlights the morphological distinctions between southern and eastern African species of this group and epitomizes the anatomy expected of the group's last common ancestor.